Polybacterial community analysis in human conjunctiva through 16S rRNA gene libraries. (September 2018) - Deepthi, KrishnanNair Geetha; Jayasudha, Rajagopalaboopathi; Girish, Rameshan Nair; Manikandan, Palanisamy; Ram, Rammohan; Narendran, Venkatapathy; Prabagaran, Solai Ramatchandirane
Abstract: The conjunctival sac of healthy human harbours a variety of microorganisms. When the eye is compromised, an occasional inadvertent spread happens to the adjacent tissue, resulting in bacterial ocular infections. Microbiological investigation of the conjunctival swab is one of the broadly used modality to study the aetiological agent of conjunctiva. However, most of the time such methods yield unsatisfactory results. Hence, the present study intends to identify the bacterial community in human conjunctiva of pre-operative subjects through 16S rRNA gene libraries. Out of 45 samples collected from preoperative patients undergoing cataract surgery, 36 libraries were constructed with bacterial nested-PCR-positive samples. The representative clones with unique restriction pattern were generated through Amplified Ribosomal DNA Restriction Analysis (ARDRA) which were sequenced for phylogenetic affiliation. A total of 211 representative clones were obtained which were distributed in phyla Actinobacteria, Firmicutes, α- Proteobacteria, β- Proteobacteria, γ- Proteobacteria, Bacteroidetes, and Deinococcus–Thermus. Findings revealed the presence of polybacterial community, especially in some cases even though no bacterium or a single bacterium alone was identified through cultivable method. Remarkably, we identified 17 species which have never been reported in any ocular infections. The sequencing data reported 6 unidentified bacteria suggesting the possibility of novel organisms in the sample. Since, polybacterial community has been identified consisting of both gram positive and gram negative bacteria, a broad spectrum antibiotic therapy is advisable to the patients who are undergoing cataract surgery. Consolidated effort would significantly improve a clear understanding of the nature of microbial community in the human conjunctiva which will promote administration of appropriate antibiotic regimen and also help in the development of oligonucleotide probes to screen the predominant pathogens for early predisposition. Highlights: An extensive molecular approach to investigate bacterial spectrum of eye microflora. Nested-PCR to detect bacteria even at low titre from swab sample. Polybacterial community identified through 16S rRNA gene libraries. Study aids better understanding while administering broad spectrum antibiotics.